Improving Overall usage of Servers by Measuring Uneven Utiliztion of a Server and allocating the Applications in the Face of Multidimensional Resource Constraints - Sonkar, SK; Kharat, MU (International Journal of Computer Sciences and Engineering, 2018)
Major objective of cloud provider is to maximize the resource utilization of cloud servers as well as to reduce the energy consumption and operative cost of the datacenter. However, the servers in many existing datacenters are underutilized in practice due to over-provisioning of peak demand. Many times, the datacenter come across situations wherein large number of application requests simultaneously demand multidimensional resources such as CPU, memory, bandwidth. In such situations it is highly impractical for the cloud service provider to satisfy the application requests of all the users within stipulated time, especially when sufficient resources are not available with them. In order to address this problem, we designed a system which measures the resource utilization of all servers before allocating the application requests to server and then dynamically allocate the application requests to the server which is underutilized. This yields in improving the overall utilization of servers. Our system initially checks the server utilization in terms of CPU, Memory and Bandwidth resource utilization against predefined threshold value. If resource of any server goes beyond its threshold value, then application request will not be allocated to that server to avoid the server overloading. That means our system redirect the application request to the underutilized server so as to improve the server resource utilization in the face of multidimensional resource constraints. The experimental results demonstrate that our system improves the overall server resource utilization by 10%.